The Influence Intervening of Trust on Purchase Intention with the Moderating Effect of Gender - Ruminda, Marthaleina; Yuliantini, Yuliantini; Keke, Yulianti; Indriyati, Indriyati; Yulihapsari, Ika Utami (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
High-quality information and services are expected to increase customer confidence in the online market. Customer trust is expected to increase customer buying interest, regardless of gender. This study aims to investigate the increase in consumer buying interest through trust as an intervening variable and gender as a moderation variable. The population in this study is online market customers. Meanwhile, the research sample amounted to 306 customers located in the Jakarta area. This study uses a quantitative descriptive method. Validity tests and reliability tests are carried out to find out that the indicators used meet the research requirements. Next, a research model test was carried out. The data analysis techniques used include path analysis and Structural Equation Modeling (SEM). Test the model using SmartPLS 4 software. The study found that high-quality information and services significantly increased customer buying interest. The results of the direct hypothesis test and the hypothesis test were not directly accepted, except for the indirect hypothesis test regarding the indirect influence of confidence on buying interest moderated by gender variables. Further research is expected to develop similar research variables and indicators so that it can strengthen the results of this research.